2020
DOI: 10.2169/internalmedicine.4287-19
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Door-to-balloon Time and Mid-term Clinical Outcomes in Patients with ST-Segment Elevation Myocardial Infarction

Abstract: Objective In primary percutaneous coronary intervention (PCI), the door-to-balloon time (DTBT) is known to be associated with in-hospital death in patients with ST-segment elevation myocardial infarction (STEMI). However, little is known regarding the association between the DTBT and the mid-term clinical outcomes in patients with STEMI. The purpose of this study was to investigate the association between the DTBT and mid-term all-cause death. Methods The study populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…We investigated an onset time from our hospital records. In cases when the time of onset was described in ambiguous terms as just getting up, morning, noon, evening, bedtime, or mid-night in clinical records, those expressions were converted to specific times to calculate onset-to-balloon time as follows: Getting up as 6:00 am, morning as 9:00 am, noon as 12:00 pm, evening as 18:00 pm, bedtime as 21:00 pm, mid-night as 0:00 am [ 22 ]. We calculated onset-to-balloon time by 2 ways: (1) using all data as mentioned above and (2) using only the exact onset time, which excluded cases without the exact onset time.…”
Section: Definitionsmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated an onset time from our hospital records. In cases when the time of onset was described in ambiguous terms as just getting up, morning, noon, evening, bedtime, or mid-night in clinical records, those expressions were converted to specific times to calculate onset-to-balloon time as follows: Getting up as 6:00 am, morning as 9:00 am, noon as 12:00 pm, evening as 18:00 pm, bedtime as 21:00 pm, mid-night as 0:00 am [ 22 ]. We calculated onset-to-balloon time by 2 ways: (1) using all data as mentioned above and (2) using only the exact onset time, which excluded cases without the exact onset time.…”
Section: Definitionsmentioning
confidence: 99%
“…We calculated onset-to-balloon time by 2 ways: (1) using all data as mentioned above and (2) using only the exact onset time, which excluded cases without the exact onset time. We defined a DTBT as the time from hospital arrival to the time of balloon dilation or thrombus aspiration [ 22 ].…”
Section: Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Referred patients were reported to have a prolonged onset-to-door time because they came from a nearby clinic or were transferred from non-PCI-capable facilities. [14,19] Previous studies reported that the time interval from an AMI onset to ventricular septal perforation manifestation had a bimodal distribution; therefore, a longer ischemic time can become a risk factor for mechanical complications due to interactions with unknown factors. [10,22] In contrast, there was a significantly shorter door-to-balloon time in referred patients with STEMI after the pandemic declaration.…”
Section: Discussionmentioning
confidence: 99%
“…Onset-to-door time and door-to-balloon time were defined as the time from symptom onset to hospital arrival and from hospital arrival to balloon dilation or thrombus aspiration, respectively. [19] In the present study, renal dysfunction was defined as creatinine level >1.5 mg/dL. Left ventricular ejection fraction (LVEF) was assessed using echocardiography.…”
Section: Definitionsmentioning
confidence: 99%